-k+6=42+3k

Simple and best practice solution for -k+6=42+3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -k+6=42+3k equation:


k in (-oo:+oo)

6-k = 3*k+42 // - 3*k+42

6-k-(3*k)-42 = 0

6-k-3*k-42 = 0

-4*k-36 = 0 // + 36

-4*k = 36 // : -4

k = 36/(-4)

k = -9

k = -9

See similar equations:

| 4w+9=2w+29 | | 9+4d=3d+12 | | 6+7a=3a-22 | | 6w+9=33+3w | | x^2+3x+4=8 | | 44/7+88=b | | -2-5x=x-44 | | 9+7x=x+15 | | d+7=40+4d | | 3d-9=0+6d | | 5a+6=-54-7a | | 3m-9=m-1 | | 3d-8=-5+6d | | 3y^2-13y+4= | | -10(-9x)= | | x^2+8x-11=9x-5 | | 62/7*20=y | | -10(9x)= | | 6m-5=4m+17 | | -m-10=-3+6m | | w-5=6w-50 | | 3+3a=5a-5 | | 4d+6=-14+6d | | -6d+3=-96+5d | | 5b+1=91-5b | | 5x*3=51 | | 21-y=7 | | 8-4a=-5a+9 | | -9+6x=7x-14 | | -2+2d=3d-10 | | -3t+5=-t-17 | | 7+5k=-4k+7 |

Equations solver categories